Uma reflexão sobre questões de gênero em uma escola pública na cidade de Goiânia através da personagem Dawn Davenport em duas cenas do filme Problemas Femininos - Oliveira, Alex Mateus Santos de (2014)
This dissertation seeks to analyze the lack of discussion and information about sex, sexuality and gender in the Brazilians schools by studying two scenes of the film “Problemas Femininos”. It identifies that when included in the academic curriculum the subject is only addressed on a biologic and / or existentialist view. By researching and analyzing the most current theories and discussions about the theme I try to understand why the Colégio Pré-Universitário located in Goiania-Goias-Brazil keep the discussion about sex, sexuality and gender out of its academic curriculum. The qualitative research is based on the processes of interpretation and the data used in this research was gathered by semi-structured interviews and focus group discussions of five 16-years-old students of a Brazilian public school. The theoretical research analyzes the feminist’s and queer’s theory and current discussions in order to deconstruct and clarify certain social practices and discourses about the theme, moreover, this dissertation points the importance of visual culture criticism to educate students about sex, sexuality and gender. My research findings prove that the schools face major obstacles to insert the discussion about sex, sexuality and gender in the academic curriculum due the diverse experience, aspirations and sociocultural background of its students which tend to increase the lack of dialogue among them.